MORAL VALUES IN NARRATIVE TEXTS OF ENGLISH TEXTBOOKS FOR SENIOR HIGH SCHOOL STUDENTS PUBLISHED BY THE MINISTRY OF EDUCATION AND CULTURE - Iwan Setiawan; Fahriany Fahriany (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT This study aimed to reveal the moral values in the narrative texts of English textbooks for senior high school students published by the Ministry of Education and Culture and also the English teachers’ and students’ responses at SMK Triguna Utama, South Tangerang City, related to the topic under investigation. This research used content analysis design. The data sources were the narrative texts in the English textbooks and teachers’ and students’ responses. The data were collected through documentation, interview, and questionnaire. Data analysis procedures consisted of perusing, eliciting, coding, tabulating, interpreting, drawing conclusions and validating. The research found that the English textbooks lacked fables and gave a smaller portion to Indonesian local stories. Moreover, the narrative texts were dominated by the value of kindness, while, fairness was included least explicitly in the stories. These findings were supported by the views and preferences of the teachers and students. Lastly, the teachers and students compactly argued that vocabulary is the greatest barrier to teaching and learning narrative text, and the effectiveness of the school’s atmosphere in instilling moral values still needed further research. ABSTRAK Penelitian ini bertujuan untuk mengungkap nilai-nilai moral dalam teks naratif buku teks bahasa Inggris untuk siswa Sekolah Menengah Atas yang diterbitkan oleh Kementerian Pendidikan dan Kebudayaan dan juga tanggapan guru dan siswa bahasa Inggris di SMK Triguna Utama, Kota Tangerang Selatan, terkait dengan topik yang diselidiki. Penelitian ini menggunakan desain analisis isi. Sumber datanya adalah teks naratif dalam buku teks bahasa Inggris dan tanggapan guru dan siswa. Data dikumpulkan melalui dokumentasi, wawancara dan angket. Sedangkan, prosedur analisis data meliputi pembacaan teks secara cermat, pemilahan data, penyandian, tabulasi, interpretasi, penarikan simpulan dan validasi. Penelitian ini menemukan bahwa buku teks bahasa Inggris tersebut masih kekurangan fabel dan cerita lokal Indonesia. Selain itu, teks naratif didominasi oleh nilai kebaikan, sementara nilai keadilan kurang tergambarkan dalam cerita. Temuan ini didukung oleh pandangan dan preferensi para guru dan siswa. Terakhir, para guru dan siswa secara sepakat berpendapat bahwa kosa kata merupakan penghalang terbesar dalam pengajaran dan pembelajaran teks naratif, dan efektivitas atmosfer sekolah dalam menanamkan nilai moral masih memerlukan penelitian lebih lanjut. How to Cite: Setiawan, I., Fahriany. (2017). Moral Values in Narrative Texts of English Textbooks for Senior High School Students Published by the Ministry of Education and Culture. IJEE (Indonesian Journal of English Education), 4(2), 130-143. doi:10.15408/ijee.v4i2.5977